Students' Perception on the Use of Wordwall for Reading Assessment: Students' Perception on the Use of Wordwall for Reading Assessment - Janadah, Cindy; Ana Ahsana , El-Sulukiyyah (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
The study explores students' perceptions of using the Wordwall application for reading assessment in an eleventh-grade AB-1 English class at SMAN 1 Gondang Wetan. It highlights the importance of reading in English learning and how technology can boost engagement and comprehension. Wordwall, an interactive online platform, allows teachers to create engaging quizzes and activities, making learning more dynamic and enjoyable. English reading skills are crucial for understanding texts, expanding vocabulary, and improving communication. In Indonesian high schools, reading assessment covers comprehension, inference, analysis, and student responses. Traditional methods often result in student struggles due to uninteresting materials and lack of innovation. Wordwall addresses these issues by offering interactive and engaging activities through various templates. Data was collected using questionnaires and interviews. The questionnaires covered the utility of Wordwall, students' enjoyment of reading on it, its effectiveness as a reading examination medium, and students' motivation. The findings showed a majority of students perceived Wordwall positively, with many agreeing it effectively examined reading skills and increased engagement. Students appreciated its accessibility and the variety of features, though some found the timer in quizzes challenging. In conclusion, the study found Wordwall to be an effective tool for reading assessment, enhancing engagement, flexibility, and providing diverse learning features. The positive student perceptions highlight the value of integrating digital tools into education. Future research should explore its broader application in developing other language skills and its comparative effectiveness against other educational technologies.